Evaluating a Psychological First Aid Training Intervention (Preparing Me) to Support the Mental Health and Wellbeing of Chinese Healthcare Workers During Healthcare Emergencies: Protocol for a Randomized Controlled Feasibility Trial - Wang, Ling; Norman, Ian; Xiao, Tao; Li, Yamin; Li, Xizhao; Leamy, Mary (Frontiers in Psychiatry, 2022)
Aims/Background: The mental health challenges faced by frontline healthcare workers responding to emergencies have become a prominent public concern. Despite the consensus that Psychological First Aid (PFA) training can effectively support public mental health during emergencies through reducing acute distress and improving self-efficacy, yet it is concerning that previous flexible delivery and neglect for evaluating PFA training has resulted in unintended potential harms which may prevent further proactive uptake of this mental health prevention strategies. Establishing the feasibility of the PFA training through adapting to the local culture, tailoring to frontline healthcare context, and evaluating systematically may be helpful to inform a large trial, or ensure effective and sustained training delivery. This study aims to present a protocol for evaluating the feasibility and acceptability of a well-adapted PFA training intervention (Preparing Me) to address the implementation gap in this mental health promotion approach. Method: This is a two-armed feasibility randomized controlled trial to be conducted among 80 Chinese frontline healthcare workers without prior related mental health training. Participants from the intervention group will receive an adapted PFA training program tailored to the Chinese frontline context to improve their knowledge and skills to support people in crisis. The primary objectives are to evaluate the training intervention’s feasibility and the target population’s acceptance of this educational intervention. The secondary objective is to obtain preliminary estimates of variability in participants’ outcomes over a 3-month period. Measurements are taken pre-intervention (T0), post-intervention (T1), and at 1- and 3-month follow-up (T2-T3). A process evaluation using qualitative research with a subgroup of trainees, their clinical managers as well as trainers will be conducted to gain a comprehensive understanding of the intervention’s acceptability and feasibility. Discussion: This present study protocol will help to establish whether this adapted PFA training intervention is feasible and accepted by the frontline healthcare workers, in preparation for a later effectiveness trial. It is anticipated that the resulted information would be an impetus to maximize usability and acceptance of this low-intensity PFA skillset by a wider population, thus supporting the mental health of frontline healthcare workers in dealing with crises for future emergencies.